Supporting students to use social media and comply with professional standards. Issue 8 (17th November 2017) - Cartwright, Luke
Abstract: Student social workers live in a world where sharing of information seems to be straightforward and unproblematic. However, data sharing is a contentious issue in practice that raises ethical issues. There is a focus on this aspect of practice in social work education particularly in the context of data storage, confidentiality and multi-disciplinary work. There have been examples of qualified workers being sanctioned by the Health Care Professions Council for breaching professional standards related to inappropriate use of social media. Understanding the advantages and potential pitfalls of social media is crucial for social workers. The aim of this research was to develop an understanding about how student social workers use social media during their time at university as a tool for continuing professional development whilst balancing the need to present a professional persona. This paper reports on four themes that emerged from a study that considered social media and social work training: changing/securing profiles; using social media to support learning and development; university support; replicating earlier behaviour in the professional setting. The findings suggest student social workers are ambivalent about the use of social media both during training and as a way to support ongoing development beyond the university setting.